Clay authigenesis in carbonate-rich sediments and its impact on carbonate diagenesis. (1st April 2023) - Chanda, Piyali; Kohli, Arjun; Teng, Fang-Zhen; Fantle, Matthew S.
Abstract: The Mg ( δ 26 M g ), Ca ( δ 44 C a ), and Sr ( 87 S r / 86 S r ) isotopic compositions of pore fluids, bulk carbonates, planktonic foraminiferal tests, and bulk clays from ODP Site 762 Hole B are presented, as are pore fluid and bulk carbonate δ 26 M g and 87 S r / 86 S r from ODP Site 806 Hole B and pore fluid δ 26 M g from ODP Site 807 Hole A. The primary objective of the study is to elucidate the major processes controlling marine pore fluid δ 26 M g, specifically the effects of calcite recrystallization and authigenic clay precipitation in sedimentary sections with relatively high carbonate contents. Such studies are critical for evaluating the potential of pore fluids in carbonate section to drive diagenetic alteration, which can compromise applications of geochemical proxies to the past. Pore fluid δ 26 M g values at all three sites range from −0.83 to −0.13‰ and exhibit a systematic increase with depth. Bulk carbonate δ 26 M g generally decrease with depth, ranging from −3.60 to −5.27‰, at Sites 762 and 806, while mixed species foraminiferal tests (∼250–500 μm) from Site 762 range between −5.08 and −4.36‰. Residual siliciclastics at depths of ∼105 to 145 mbsf at Site 762 have δ 26 M g values (−0.09 to 0.27‰) that are markedly higher than carbonate and pore fluid δ 26 M g values. Simple 1-D reactive transport modeling suggests that the general increase in pore fluid δ 26 M g with depth, accompanied by a decrease in carbonate δ 26 M g, is a result of calcite recrystallization (assuming an isotopic fractionation factor of ∼0.9955). However, subtle but significant deviations from the carbonate recrystallization-only scenario suggest that another process impacts δ 26 M g at all three sites. Scanning electron microscope images document clay particles embedded in nannofossils and foraminiferal tests at Site 762, which suggest that clay authigenesis is active in carbonate sediments and could affect pore fluid δ 26 M g . The formation of secondary clays preferentially sequesters isotopically heavy Mg ( α clay - M g 2 + ≈ 1.0005 ), driving pore fluid δ 26 M g to lower values. An increase in carbonate δ 26 M g within the clay-rich layer at Site 762 and an increase in bulk carbonate Na/Ca supports the hypothesis that clay authigenesis also impacts the preservation of proxy archives. Multi-component reactive transport modeling suggests that authigenic rates of ∼1·10 −13 mol/m 3 /s (∼3.15 µmol/m 3 /a; assuming that the authigenic clay is sepiolite) can generate deviations from the carbonate recrystallization-only case by several tenths of a permil, indicating that carbonate sediment-associated clay authigenesis (CSCA) may be more relevant in deep-sea carbonate sections than has been previously considered.